2016
DOI: 10.1167/16.14.4
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous density contrast is bidirectional

Abstract: Simultaneous density contrast, or SDC, is the phenomenon in which the perceived density of a textured region is altered by a surround of different density (Mackay, 1973). SDC provides an experimental tool to investigate mechanisms of density coding, yet has not been systematically examined. We measured SDC with a 2AFC staircase procedure in which human observers judged which of two patterns, one with and one without a surround, appeared more dense. We used a range of surround densities varying from very sparse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(28 citation statements)
references
References 50 publications
5
23
0
Order By: Relevance
“…Note that the high numerosity conditions in these studies may fall into the density regime as well (Aida et al, 2015;Burr & Ross, 2008). Also one should note that other studies have suggested a common basis for coding density and numerosity (Dakin et al, 2011;Morgan et al, 2014;Raphael & Morgan, 2016;Sun et al, 2016;Sun et al, 2017;Tibber et al, 2012). Therefore, it remains unclear whether depth can affect density perception directly.…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…Note that the high numerosity conditions in these studies may fall into the density regime as well (Aida et al, 2015;Burr & Ross, 2008). Also one should note that other studies have suggested a common basis for coding density and numerosity (Dakin et al, 2011;Morgan et al, 2014;Raphael & Morgan, 2016;Sun et al, 2016;Sun et al, 2017;Tibber et al, 2012). Therefore, it remains unclear whether depth can affect density perception directly.…”
Section: Introductionmentioning
confidence: 74%
“…Stimuli consisted of quasi-randomly placed, nonoverlapping uniform discs, termed dots, as described in our previous studies (Sun et al, 2016;Sun et al, 2017). Half of the dots were black (7 cd/m 2 ) and half white (115 cd/m 2 ), each with a diameter of 0.058, and placed on a mid-gray background of 61 cd/m 2 .…”
Section: Stimulimentioning
confidence: 99%
See 3 more Smart Citations